2021
DOI: 10.1101/2021.11.29.470344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General factors of white matter microstructure from DTI and NODDI in the developing brain

Abstract: Preterm birth is closely associated with diffuse white matter dysmaturation inferred from diffusion MRI and neurocognitive impairment in childhood. Diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) are distinct dMRI modalities, yet metrics derived from these two methods share variance across tracts. This raises the hypothesis that dimensionality reduction approaches may provide efficient whole-brain estimates of white matter microstructure that capture (dys)maturatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…In this work, we demonstrate that the VB index can be used to explore graded changes in the microstructural properties of the neonatal cortex. Consistent with previous descriptions of the dysmaturation following preterm birth as a substantially whole-brain phenomenon ( Telford et al, 2017 ; Blesa et al, 2020 ; Vaher et al, 2022 ), across two independent datasets we find that a significant proportion of cortical microstructure is consistently altered in association with preterm birth, in a spatially distributed rather than localised fashion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this work, we demonstrate that the VB index can be used to explore graded changes in the microstructural properties of the neonatal cortex. Consistent with previous descriptions of the dysmaturation following preterm birth as a substantially whole-brain phenomenon ( Telford et al, 2017 ; Blesa et al, 2020 ; Vaher et al, 2022 ), across two independent datasets we find that a significant proportion of cortical microstructure is consistently altered in association with preterm birth, in a spatially distributed rather than localised fashion.…”
Section: Discussionsupporting
confidence: 90%
“…Imaging of the preterm brain at term-equivalent age has characterised dysmaturation following preterm birth as a global phenomenon (i.e. encompassing the whole brain), with generalised dysconnectivity and atypical topology of developing neural networks, increased water diffusivity, altered white matter microstructure and reduced brain volume and cortical surface area ( Telford et al, 2017 ; Batalle et al, 2018 ; Boardman and Counsell, 2019 ; Blesa et al, 2021 ; Vaher et al, 2022 ). Motivated by the search of neural antecedents of cognitive impairment observed in some preterm born individuals, studies focusing on the neonatal cortex have demonstrated that prematurity impacts cortical growth and microstructural development in a dose-dependent fashion ( Kapellou et al, 2006 ; Ball et al, 2013b ) and that preterm birth alters cortical folding ( Shimony et al, 2016 ; Neil and Smyser, 2018 ; Dubois et al, 2019 ), thalamo-cortical connectivity ( Boardman et al, 2006 ; Ball et al, 2013a ), and different regional MRI metrics with varying spatial distribution, including water diffusion measures, markers of myelination and cortical morphology metrics ( Bouyssi-Kobar et al, 2018 ; Ouyang et al, 2019 ; Ball et al, 2020 ; Dimitrova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in six microstructure metrics for three tracts for all 51 participants. These diffusion measures were reduced through PCA into microstructurally informative features (Chamberland et al, 2019; Geeraert et al, 2020; see also Gagnon et al, 2022; Guberman et al, 2022; Vaher et al, 2022). The tract microstructure data were combined in a single table.…”
Section: Methodsmentioning
confidence: 99%
“…As above, details of individual white matter tract segmentation and subsequent extract of tractaveraged dMRI metrics have been outlined previously from infants from this study sample (79).…”
Section: Tract Segmentation and Extraction Of Tract-averaged Dmri Met...mentioning
confidence: 99%
“…dMRI measures of white matter appear to be highly correlated (e.g. high FA in an individual tract such as the arcuate fasciculus is often accompanied by high FA across all other white matter tracts in that individual), a property that persists from early infancy through to older age (79,86,87). As a result of this, it is common to derive general factors (g-factors) of white matter microstructure to characterise global white matter microstructure.…”
Section: Dnam Crp and Dmri White Matter Tract Associationsmentioning
confidence: 99%